PARTICULARITĂŢI DE TRADUCERE A TEXTULUI MEDICAL DIN LIMBA ITALIANĂ ÎN LIMBILE ROMÂNĂ ŞI ENGLEZĂ - Şeremet, Aurelia (CEP USM, 2013)
The study highlights (simultaneously in three languages) the aspects of the Italian, Romanian and English medical language, the English influence on the evolution of medical language of Greco-Roman origin; the deepening and theoretical development of the necessary information to the translators of medical texts; the grounding of the formation procedures of the specialized medical vocabulary – the metaphor and periphrasis; the comparative analysis of medical terms and their conceptualization in the three languages research through the traditional etymology (Greek and Latin) and from contemporary North-Occidental point of view.
Keywords: traducere